Detection and comparison of fetal malnutrition by CANSCORE and other methods - Dhanorkar, Abhaykumar Balajirao; Bagdey, Prashant; Humne, Arun; Ughade, Suresh; Yadav, Seema Prakash; Khadse, Amol Dadarao (International Journal of Research in Medical Sciences, 2017)
Background: Objective of current study was clinical assessment of nutritional status of neonate using CANSCORE and comparison with other methods of determining fetal malnutrition. Design: Cross sectional study. Setting: Tertiary care hospital. Study subjects: 384 live born singleton neonates with known gestational age and no major congenital malformation. Methods: Birth weight, length, midarm circumference and head circumference recorded in new-borns. Ponderal index and mid arm to head circumference ratio was calculated. Clinical assessment of nutritional status was done on the basis of CANSCORE and compared with other methods. Results: CANSCORE <25 separated 67.71% of the babies as well-nourished and 32.29% as malnourished. Weight for age and MAC/HC classified nearly 70% of babies as well-nourished and 30% as malnourished. Also Ponderal index classified 75.52% the babies as well-nourished and 24.48% as malnourished. Conclusion: CANSCORE may be a simple clinical index for identifying fetal malnutrition and for prediction of neonatal morbidity associated with it, without the aid of any sophisticated equipments.